Evaluating Translation in the Algerian English Language Public School Textbooks - Slimane Boukhentache (The Journal of Studies in Language, Culture and Society)
New trends in language teaching recognize the value of translation as a pedagogical tool and as a social skill. New translation activities have been formulated to substantiate translation pedagogies. While most studies focus on code switching, a few studies analyzed the translation activities in the textbooks. This study used content analysis to investigate the extent to which translation activities are used in Algerian English language public school textbooks. The findings indicate that the textbooks are hardly integrating bilingual activities. Additionally, the existing activities are tentative and linguistically-driven; furthermore, they are a way from tapping at the development of communicative competence and bilingual/multilingual competencies. Consequently, it is strongly recommended to integrate more functional activities into the textbooks and standardize this pedagogical practice.